Providing cell phone numbers and email addresses to Patients: the physician's perspective - Freud Tamar; Avdalimov Angelika; Peleg Roni (BMC Research Notes, 2011)
Abstract Background The provision of cell phone numbers and email addresses enhances the accessibility of medical consultations, but can add to the burden of physicians' routine clinical practice and affect their free time. The objective was to assess the attitudes of physicians to providing their telephone number or email address to patients. Methods Primary care physicians in the southern region of Israel completed a structured questionnaire that related to the study objective. Results The study population included 120 primary care physicians with a mean age of 41.2 ± 8.5, 88 of them women (73.3%). Physicians preferred to provide their cell phone number rather than their email address (P = 0.0007). They preferred to answer their cell phones only during the daytime and at predetermined times, but would answer email most hours of the day, including weekends and holidays (P = 0.001). More physicians (79.7%) would have preferred allotted time for email communication than allotted time for cell phone communication (50%). However, they felt that email communication was more likely to lead to miscommunication than telephone calls (P = 0.0001). There were no differences between male and female physicians on the provision of cell phone numbers or email addresses to patients. Older physicians were more prepared to provide cell phone numbers that younger ones (P = 0.039). Conclusions The attitude of participating physicians was to provide their cell phone number or email address to some of their patients, but most of them preferred to give out their cell phone number.